Confidentiality and transparency in the judicial inspection works. the case of the Republic of Moldova - Creciun, Natalia (Tipografia "CentroGrafic" SRL,Cahul, 2020)
The general findings of the present paper refer to the fact that the overall activity of the judicial inspection body is confidential. However, there are also transparent activities, due to the necessity of alignment of the judicial inspection body to the policies of good judicial self-government, that presuppose the openness of public authorities, including the Judicial Authority, towards the society. Thus, the competencies of the judicial inspection body should be exercised in a manner that ensures the balance between confidentiality and transparency, in order to protect the independence and the reputation of judges, as well as the public interest, as an immanent element of the public confidence in the Judiciary.

Constatările generale ale prezentei lucrări se referă la faptul că activitatea de ansamblu a organului de inspecție judiciară este confidențială. Totuși, există și activități transparente, datorită necesității de aliniere a organului de inspecție judiciară la politicile de bună autoguvernare judiciară, care presupun deschiderea autorităților publice, inclusiv a Autorității Judecătorești, față de societate. Astfel, organul de inspecție judiciară ar trebui să-și exercite competențele într-o manieră care să asigure echilibrul dintre confidențialitate și transparență, în scopul protejării independenței și a reputației judecătorilor, precum și interesul public, in calitate de element imanent al încrederii publice în Magistratură.
CONFIDENȚIALITATE ȘI TRANSPARENȚĂ ÎN LUCRĂRILE DE INSPECȚIE JUDICIARĂ. CAZUL REPUBLICII MOLDOVA
Keywords: Judicial Inspection; confidentiality; transparency; Inspecția Judiciară; confidențialitate; transparență